IMPLEMENTASI MEDIA DIGITAL INTERAKTIF BERBASIS CANVA UNTUK MENINGKATKAN PEMAHAMAN TEKS NARASI SISWA KELAS III SEKOLAH DASAR KRISTEN HARMONI - Reza Marseila Tabe, Getruida Pookey, Rian Ismael Adu; Defrianti Wae Henakin, Fasti Vivinda Runesi, Indrawati Huan; Metilda Kofi, Petronela Uduk, Heryon Bernad Mbuik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop and implement an interactive digital media based on Canva to improve the narrative text comprehension of third-grade elementary school students. The background of this study is the lack of interactive media used in Indonesian language learning, which makes students less motivated and causes difficulties in understanding narrative texts. This research used the Research and Development (R&D) method with the ADDIE model, including Analysis, Design, Development, Implementation, and Evaluation stages. The product developed is an interactive media integrating images, animations, narration, and interactive exercises. The media was validated by material, media, and language experts and tested on 20 students at SDK Harmoni Kupang. Data collection techniques included observation, questionnaires, and pretest-posttest. The results showed a significant increase in students' understanding of narrative text. The average pretest score was 59, while the posttest average rose to 82.5, with an N-Gain score of 0.57 (moderate category). Statistical analysis indicated that the data were normally distributed and homogeneous, and there was a significant linear relationship between media use and learning outcomes. The media not only improved students' comprehension of narrative texts but also increased learning motivation, collaboration, and critical thinking skills.